Influencing factor analysis of family doctor contract service among older adults: evidence from China - Xie, Shiyu; Ni, Zihan; Yang, Xiya; Xu, Ningze; Zhu, Chengfang; Huo, Liting; Zhu, Xiuyuan; Yang, Xiaoguang (Frontiers in Public Health, 2024)
BackgroundFamily doctor contract services are essential to primary healthcare and play a significant role in improving the health of older adults. However, contract rates among older adults vary widely. Investigating the factors influencing contract rates is crucial for optimizing policies and increasing participation in family doctor services.MethodsThis study used data from Wangying Community Health Service Center, encompassing 5,684 older adults in 2018. To address the endogeneity issue arising from sample selection bias, the study utilized a 1:1 nearest-neighbor matching method for counterfactual testing, balancing potential confounding factors between the contract and non-contract groups. Subsequently, multiple logistic regression analysis was performed on the matched data to explore the impact of gender, age, number of medical visits, and the number of chronic conditions on family doctor contract behavior.ResultsGender did not significantly impact contracting behavior. However, age, the number of medical visits, and the number of chronic diseases significantly influenced family doctor contract (β = 0.457, p < 0.01; β = 0.286, p < 0.05; β = −0.229, p < 0.1). An inverted U-shaped relationship was found between age and contracting behavior (β = −0.003, p < 0.01).ConclusionThe factors influencing older residents’ decisions to sign up for family doctor services are complex and diverse. The conclusion of the study provides valuable reference and guidance for policymakers to further improve the family doctor contracting system and optimize contracting strategies by considering the characteristics of different older adults.